Aberrations in the mismatch repair genes and the clinical impact on oesophageal squamous carcinomas from a high incidence area in South Africa. Issue 3 (25th February 2005) - Naidoo, R; Ramburan, A; Reddi, A; Chetty, R
Abstract : Aims: To investigate the incidence of genetic aberrations in the DNA repair genes in a cohort of oesophageal cancers. Methods: One hundred oesophagectomy samples of squamous cell carcinoma were studied. Normal and tumour DNA were isolated using a standard phenol/chloroform extraction procedure. Six recommended microsatellite loci with high informativity were analysed. The following markers were used: D2S123 (2p), D3S659 (3p), D3S1255 (3p), Bat 25 (4q), Bat 26 (2p), and Bat 40 (1p). The results were analysed using software attached to an automated DNA sequencer. The molecular data were then correlated with clinicopathological parameters. Results: The incidence of microsatellite instability and loss of heterozygosity was very low. There was no significant correlation between the clinicopathological and molecular data. However, D2S123 genetic abnormalities were seen more frequently in both moderately and well differentiated tumours than in poorly differentiated tumours (p = 0.033). Follow up data were available for only 67 of the 100 patients. Fifty patients were alive and 17 patients had died. Conclusion: Low frequencies of genetic aberrations in these mismatch repair loci are found in squamous carcinomas of the oesophagus from a high incidence area in South Africa.